Features of communication between the stage director and members of the group during the preparation of choreographic performances - Andriitso, Vasyl M.; Tsyhanyk, Myroslava I.; Shevtsova, Iryna M.; Shiutiv, Mykhailo A.; Kutsyk, Oleksandr P. (Linguistics and Culture Review, 2021)
Communication is the cornerstone of co-production, and the director is the cornerstone that brings together the different parts of communication. Basically, communication is "the process of exchanging information between people through a common system of symbols, signs or behaviour". A director does everything in a form of communication during a production. Whether it's blocking, scheduling rehearsals or calling a show; communication is as "vital to stage management as memorisation is to artistic skill". Communication allows the production director to effectively manage the production. Since communication is a broad topic, this study will first consider the two forms of communication that the production director uses, how these skills can be applied to very specific communication aspects and what these benefits look like. This study examines the works on the development of choreographic art, the development of personality within a dance group, and the features of interaction between members of a large artistic group while working on a production. As a result, the most effective methods of communication between the participants of the choreographic performance were discussed.